Analisis Perbandingan Hasil Belajar PPKn Kelas IV Pada Kurikulum Merdeka Dan Kurikulum 2013 - Via Luftiatun Nabila; Yuyut Yuyut; Sabila Samkor; Valestine Fitria Devitasari (MISOOL: Jurnal Pendidikan Dasar, 2020)
This study aims to compare the learning outcomes of pancasila and citizenship education (PPKn) subjects between grade IV students who follow the merdeka curriculum and the 2013 curriculum. The background of this study is based on the differences in pedagogical approaches between the two curricula, as well as the importance of examining the effectiveness of curriculum implementation in improving students’ academic achievement. The study used a quantitative approach with a comparative design. The subjects of the study consisted of students of SD Inpres 17 Sorong regency (merdeka curriculum) and MI AL Ishlah Sorong city (2013 curriculum). Data were obtained through documentation of mid-semester exam (UTS) scores and analysed using an independent t-test with the help of SPSS software. The results of the analysis showed a significant difference between the two groups (p = 0.006686), where students who followed the merdeka curriculum obtained higher UTS scores. These findings indicate that the flexible and contextual approach in the merdeka curriculum is more effective in improving student learning outcomes in PPKn subjects. This research provides an empirical contribution to the decision-making of curriculum policies and learning strategies that are more adaptive to the needs of students at the elementary education level.